METODE PEMBUATAN PLANKTON NET SEDERHANA - Nunung Komalawati (Integrated Lab Journal, 2016)
Plankton nets are used for planktonic aquatic organism collection. It has been widely used for long time on research and education at higher education, especially in the field of aquatic biology, fisheries and marine biology, and aquatic ecology. Therefore, manufactured and standard plankton nets are available. However, some laboratories have limited number of such manufactured plankton nets due to its high price. Handmade plankton nets are good alternative to provide reasonable number of plankton nets for research and education. Qualified handmade plankton nets are needed to ensure that qualified data are obtained. The aim of producing of plankton nets was to obtain handmade plankton nets with data quality similar to the data from manufactured plankton nets. Handmade plankton nets were designed to have a similar mesh size to common manufactured plankton nets that was No. 25. However, it has different specification to other manufactured plankton nets such as ORI and MDH plankton nets. Field examination has proven that data quality resulted by handmade plankton nets were not significantly different. This was due to that both handmade and manufactured plankton nets had a same mesh size. Data quality for plankton collections are depends on mesh size and plankton abundance in the water ecosystem, rather than depend on hand made or manufactured.